Preparation and anticoagulant activity of functionalised silk fibroin. (18th May 2019) - Shi, Pange; Zhang, Ling; Tian, Wei; Li, Helei; Wang, Qiongyu; Yi, Honggen; Yin, Yin; Wang, Aiqing; Ning, Ping; Dong, Fenglin; Wang, Jiannan
Graphical abstract: Highlights: Negatively charged SF was cationically modified with NH2 -PEG-NH2 . Effective loading of hirudin on cationic SF films was very high. Functionalised SF films markedly prolonged the activated partial thrombin time. Functionalised SF films significantly inhibited platelets adhesion and activation. Functionalised SF films maintain high thrombin inhibition activity. Abstract: Firstly, negatively charged silk fibroin (SF) was cationically modified by covalent linkage with polyethylene glycol diamine (NH2 -PEG-NH2 ). The surface charge of cationic SF film changed from negative to positive when SF:NH2 -PEG-NH2  = 100:0.5, and enhanced with increasing NH2 -PEG-NH2 . Zeta potential was maximal and stable when SF:NH2 -PEG-NH2  = 100:5. NH2 -PEG-NH2 induced SF films to adopt a stable crystalline structure. After cationisation, SF films were loaded with hirudin (SF-PEG-HIR film) by non covalent linkage. The effective load capacity of hirudin on the surface of cationic SF films was highest (>40 U/cm 2 ) when SF:NH2 -PEG-NH2  = 100:10. The ability of SF-PEG-HIR films to inhibit thrombin activity improved with increasing hirudin content while thrombin activity was reduced significantly (A405 decreased from 0.563 to 0.03) when the hirudin loading was 40 U/cm 2 . Likewise, thrombin activity in fresh plasma was reduced significantly (A405 decreased from 0.102 to 0.067). Release dynamics showed that thrombin activity decreased linearly within 2 h, then more slowly thereafter. SF-PEG-HIR films markedly prolonged the activated partial thrombin time and significantly inhibited adhesion of platelets. Thus hirudin can be stably loaded on cationic SF films via electrostatic interaction, maintaining high thrombin inhibition activity, and significantly improving the anticoagulant properties of SF films.